Risk Control Model of Paddy Rice Farming Production and Farmers’ Behavior in Tanjung Jabung Barat (Moscardi and De Janvry Approach Method) - Nainggolan, Saidin; Fitri, Yanuar; Ulma, Riri Oktari; br. Sinuraya, Cynthia Cleantha (International Journal of Environment, Agriculture and Biotechnology, 2022)
The role of rice farming in meeting rice needs is linear with the behavior of farmers responding to production risk. Farmer behavior determines the magnitude of production risk and farmer decision-making. The behavior of farmers is risk averse, risk neutral, or risk taker. Assessing the actual production function, the frontier production function, the risk function, and farmer behavior are helpful as benchmarks to make it easier to answer what factors determine the level of efficiency and use of optimal production input scenarios to achieve optimal production. The purpose of this study is (1) to analyze the response and production risk response to the use of production inputs. (2) Analyzing the behavior of farmers in responding to production risks. (3) Building a model for handling production risks and farmer behavior. The research was conducted in Tanjabbar Regency which was determined proportionally, the sample size was based on the slovin method as many as 122 farmers, and the sampling method was simple random sampling. The method of data analysis is the Cobb-Douglass production function, the Cobb-Douglass risk function, the behavior of farmers using Moscardi and De Janvry, and the production risk management model and the behavior of farmers using the kumbakar function. Cultivation technology carried out by farmers is still conventional with the use of production inputs that are still below the recommended dose. The productivity obtained by farmers is low, and the production risk is high. The determinants of the productivity function of lowland rice farming are urea, SP36, KCL, and organic fertilizers. Optimal use of these production inputs will be able to reduce the occurrence of production risk. Farmers' behavior in responding to production risks is to avoid risk and is mainly determined by the demand for urea and SP36 fertilizers. Sources of technical inefficiency mostly come from a narrow land area. Production risk control can be done by increasing productivity through the use of optimal production inputs, especially urea, SP36, and organic fertilizers, as well as the intensification of land area.